Gambaran Putus Obat Berdasarkan Sosial-Demografi pada Penderita Tuberkulosis di Indonesia Tahun 2023: Cross-Sectional Study - Yudhanti, Anindya Oktaria; Saf, Arina Syahida Hurva Radisan; Riska, Benita; Tamba, Enita Fransiska (Jurnal Epidemiologi Kesehatan Indonesia, 2025)
Introduction: Tuberculosis is an infectious disease that spreads through the air. Based on data at the international and national levels, there has been an increase. Most pulmonary TB patients are cured with consecutive antibiotic treatment for 6-9 months, but there are still patients who eventually drop out of treatment. This could be a challenge in achieving the international tuberculosis elimination target of 2035 and the national target of 2030. Methods: This study analyzed the socio-demographic distribution and dropout analysis of Tuberculosis patients in Indonesia in 2023 based on SKI data with a cross-sectional study type. Results: The incidence of drug withdrawal in the age group was due to the unavailability of drugs at health care facilities. In the male group, most (33.5%) stated that they dropped out because they felt healthy while in the female group, 38.2% stated that they dropped out because the drugs were not available at the health facilities. The incidence of drug withdrawal was also more prevalent among individuals with primary school education (38.9%), whose employment status was currently not working (34.7%), and living in urban areas (38.3%). This was due to the individuals feeling healthy. Individuals with the lowest economic status also contributed the most to the incidence of drug withdrawal with the reason for drug withdrawal due to unavailability at the health facility (36.8%). Conclusion: From this study, it was found that feeling healthy and unavailability of drugs in health facilities were the most common reasons for drug withdrawal across socio-demographic groups and choosing traditional medicine was the least common reason across socio-demographic groups.